Controlled multiple neutral planes by low elastic modulus adhesive for flexible organic photovoltaics. (19th April 2017) - Kim, Wansun; Lee, Inhwa; Yoon Kim, Dong; Yu, Youn-Yeol; Jung, Hae-Yoon; Kwon, Seyeoul; Seo Park, Weon; Kim, Taek-Soo
Abstract: To protect brittle layers in organic photovoltaic devices, the mechanical neutral plane strategy can be adopted through placing the brittle functional materials close to the neutral plane where stress and strain are zero during bending. However, previous research has been significantly limited in the location and number of materials to protect through using a single neutral plane. In this study, multiple neutral planes are generated using low elastic modulus adhesives and are controlled through quantitative analyses in order to protect the multiple brittle materials at various locations. Moreover, the protection of multiple brittle layers at various locations under both concave and convex bending directions is demonstrated. Multilayer structures that have soft adhesives are further analyzed using the finite element method analysis in order to propose guidelines for structural design when employing multiple neutral planes.